Mastectomy for Breast Cancer under Regional Anesthesia Utilizing Intertransverse Process Block in Patients Exhibiting Poor Pulmonary Function - Ghulam Murtaza Shaikh, Mohsin Riaz Askri, Eram Shahzadi, Shumyala Maqbool, Noreen Maqbool Bokhari, Muhammad Muazzam Butt (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mastectomy is a common procedure for breast cancer treatment, but in patients with poor pulmonary function, general anesthesia can pose significant risks. Objective: To assess postoperative pain management, respiratory outcomes, recovery time, and complication rates in patients with poor pulmonary function undergoing mastectomy with ITPB. Methods: This prospective cohort study was conducted at Baqai Medical University Karachi during June 2022 to June 2023. A total of 155 female patients diagnosed with breast cancer who were scheduled for mastectomy were included in the study. Patients were selected based on predefined inclusion and exclusion criteria to ensure consistency and the quality of data. Results: Postoperative pain scores decreased significantly from 3.2 ± 1.1 at 0 hours to 0.8 ± 0.4 at 24 hours. A total of 75% of patients required minimal opioid supplementation, with a mean consumption of 15.2 ± 7.1 mg morphine equivalents in the first 24 hours. Oxygen saturation remained stable, with an SpO2 of 95.8% ± 2.3% at 0 hours and 94.5% ± 2.1% at 24 hours. The time to extubation was 12.6 ± 3.2 minutes, and time to ambulation was 14.4 ± 4.3 hours. The average length of hospital stay was 3.6 ± 1.1 days. Complications were minimal, with 7% of patients reporting mild tenderness at the injection site and 0.6% experiencing a small hematoma. Conclusions: It is concluded that performing mastectomy under regional anesthesia with ITPB is a safe and effective alternative to general anesthesia in patients with compromised pulmonary function. Keywords: Mastectomy, Regional Anesthesia, Intertransverse Process Block, Pulmonary Function, Pain Management, Recovery, Complications.